ANALISIS PENGARUH KETERSEDIAAN INFRASTRUKTUR, INVESTASI, DAN ANGKATAN KERJA TERHADAP PERTUMBUHAN EKONOMI DI PULAU JAWA - Nafla Salsabila (Jurnal Paradigma Multidisipliner (JPM), 2022)
Economic growth can be seen from the development of the Gross Regional Domestic Product (GRDP) of each region and is influenced by various factors. This study aims to analyze the effect of electricity infrastructure, investment, and the workforce on economic growth. The data used is panel data obtained by the Library Research technique and analyzed by multiple regression analysis method. The results of the study indicate that the electricity infrastructure variabel has a positive but insignificant effect on economic growth, while the investment variabel and labor force variabels have a positive and significant effect on economic growth in Java. Keywords: GRDP; Infrastructure; Investation; Workforce